CALCULATION METHOD on limiting conditions OF PILES arranged USING bit-PULSE TECHNOLOGY - V. E. Bykhoutsev; V. S. Smorodin; D. V. Prokopenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An original calculation method of the CIT-piles on the bearing capacity and deformations in nonlinear-deformable earth foundation based on soil compaction in the discharge-pulse treatment zone is proposed.